2015
DOI: 10.1177/0003489415595424
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Complications After Transsphenoidal Surgery in Cushing’s Versus Non-Cushing’s Disease Patients

Abstract: Objective: Transsphenoidal surgery (TSS) harbors a potential for hypopituitarism, cerebrospinal fluid (CSF) leaks, and other complications. We utilized the Nationwide Inpatient Sample Database (NIS) to compare inpatient complication rates between Cushing's disease (CD) and non-Cushing's disease (NCD) patients undergoing TSS. Methods: Inpatient hospitalization data for 960 CD and 12 110 NCD patients who underwent TSS between 2002 and 2010 were accessed. Demographic information, outcomes, and complication rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In our sample consisting of over 10,000 patients treated in the most recent year available with NIS inpatient data, we identified an overall postoperative CSF rhinorrhea incidence of 2.6%. Despite numerous surgical advancements to address postoperative CSF leaks, including the utilization of endoscopic techniques pioneered by Wigand in 1981, our data coincide with the likes of many previously published samples characterizing extended hospital stays, additional procedures, additional anesthesia risks, and higher discharge total costs associated with this complication . Jahangiri et al reported in 2014 that repeat operations for recurring tumors or postoperative CSF leak can carry an increased risk for electrolyte abnormalities including hyponatremia and meningitis, both significantly adding to morbidity and an increased length of hospitalization .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our sample consisting of over 10,000 patients treated in the most recent year available with NIS inpatient data, we identified an overall postoperative CSF rhinorrhea incidence of 2.6%. Despite numerous surgical advancements to address postoperative CSF leaks, including the utilization of endoscopic techniques pioneered by Wigand in 1981, our data coincide with the likes of many previously published samples characterizing extended hospital stays, additional procedures, additional anesthesia risks, and higher discharge total costs associated with this complication . Jahangiri et al reported in 2014 that repeat operations for recurring tumors or postoperative CSF leak can carry an increased risk for electrolyte abnormalities including hyponatremia and meningitis, both significantly adding to morbidity and an increased length of hospitalization .…”
Section: Discussionsupporting
confidence: 85%
“…Numerous analyses characterize a link between obesity and postoperative CSF rhinorrhea following procedures on the pituitary . Dlouhy et al demonstrated that an increase in one's body mass index (BMI) of 5 kg/m 2 increased the risk of postoperative CSF rhinorrhea by 1.61 times .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSS complications have been previously characterized in various patient populations, such as those with acromegaly, Cushing's disease, and pituitary malignancies . However, the impact of obstructive sleep apnea (OSA) on TSS outcomes is a relevant concern that has not been well examined.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] TSS complications have been previously characterized in various patient populations, such as those with acromegaly, Cushing's disease, and pituitary malignancies. [5][6][7] However, the impact of obstructive sleep apnea (OSA) on TSS outcomes is a relevant concern that has not been well examined. OSA is a sleeping disorder characterized by upper airway collapse, with an incidence of 3% to 7% in the general population.…”
Section: Introductionmentioning
confidence: 99%